Beautiful Babies: Eugenic Display of the White Infant Body, 1854-1922 - Stroud, Irene (Bulletin for the study of religion, 2014)
Baby shows and baby contests in the late nineteenth century United States, beginning as a form of entertainment at agricultural fairs, were co-opted in the early twentieth century as a public relations vehicle for the eugenics movement. This article connects this history of display of the infant body with white Protestant practices of bodily display in infant baptism as represented etiquette manuals, women's magazines, and works of art. The author argues that infants became unwitting participants in practices of display that marked them as members of affluent white society.